Corporate governance and fraud: an investigation to determine whether the primary recommendations of the king report can assit in preventing management irregularities within an organisation - Benade, Dirk Christoffel (My University, 2016)
The King Report released in South Africa in 1994 has the potential to revolutionise the country's existing form of Corporate Governance. The objective of the report is to improve the system by which companies in South Africa are directed and controlled (King Report, 1994:1). This objective encompasses decreasing the risk of management fraud within entities. The question which this research report addresses is whether a reduction in the risk of management irregularities in an organisation can be achieved through adherence to the King Report's proposals. To obtain this answer a South African company which experienced significant management frauds was selected for examination as a case study, and a determination was made as to whether the proposals of the King Report, had they been implemented, could have prevented the irregularities which occurred in the organisation. The finding of the research is that diligent compliance with the King Report's recommendations can assist significantly ill both preventing and detecting management fraud, but is unlikely to prevent all management irregularities within an organisatlon
A Research Report Submitted to the Faculty of Commerce University of the Witwatersrand, Johannesburg in partial fulfilment of the requirements for the degree of Mastel of Commerce Johannesburg 1995
Keywords: Corporate governance -- South Africa.; Fraud.